PERAN GURU DALAM MENINGKATKAN INTERAKSI SOSIAL PESERTA DIDIK DENGAN LATAR BELAKANG KELUARGA BROKEN HOME DI KELAS 3 SD AL-ISLAM PENGKOL JEPARA - Lestari, Dwiyana Puji; Attalina, Syailin Nichla Choirin; Zumrotun, Erna (STKIP Persada Khatulistiwa Sintang, 2024)
This research aims to reveal the role of teachers in enhancing social interaction among students from broken homes at third grade in SD Al-Islam Pengkol Jepara. This study employs a qualitative case study approach. Data collection techniques include observation, interviews, and documentation. The findings indicate that teachers play a crucial role in improving the social interaction of these students through interactive methods, changes in seating arrangements and group assignments. A personal approach and emotional support from teachers help build students' self-confidence. Teachers also teach ways to resolve conflicts constructively and encourage active participation. With appropriate and consistent support, students from broken homes can adapt more easily and thrive in a supportive school environment.